Ending the Exploitation of Migrant Workers in the Gulf - Auwal, Mohammad A. (Tufts Archival Research Center, 2005)
Volume 34, Issue 2. Summer While the Arab Gulf states have received considerable attention for their tremendous natural-resource wealth, far less focus has been placed on the system of migrant labor that underpins their economic growth. In this revealing article, Mohammad Auwal, professor of communication studies at California State University in Los Angeles, uses first-hand accounts to shed light on the plight of migrant laborers working in the Gulf.